PUSAT LITERASI KOTA PONTIANAK - Mangenda, Yoris; Kalsum, Emilya; Br. Gultom, Bontor Jumaylinda (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2020)
Central Connecticut State University stated in 2016, Indonesia was ranked 60th out of 61 countries regarding literacy. According to UNESCO literacy is the ability to identify, understand, interpret, communicate, in various contexts. The National Alibaca Index said that most provinces in Indonesia have a low literacy index, including West Kalimantan, which is ranked 3rd out of 34 provinces. However, in Pontianak City, in the last 5 years, various literacy-based activities such as exhibitions, book fairs, discussions have been intensively held, as well as recorded more than 20 literacy communities in 2019. All literacy activities are organized independently and have no special space. Therefore, considering literacy needs and problems, the potential location for the design area is Jl. General Ahmad Yani, Pontianak City. However, there are problems where there is no standardization that can be used as a reference for designing a Literacy Center. Therefore, the design method used is the Design Thinking method, which, according to Kambel (2009), is a creative approach by gathering information and opportunities available to be synthesized into innovation and work ideas. Through this method, facilities such as exhibition rooms, classrooms, reading and collection, as well as spatial arrangements and forms are found to accommodate literacy activities in Pontianak.